Scrapping of PEKK-based thermoplastic composites retaining long fibers and their use for compression molded recycled parts - Alejandro Sandá; Rocío Ruiz; Miguel Ángel Mafé; Jon Ander Sarasua; Antonio González-Jiménez (AIMS Materials Science, 2023)
In this work, a novel method for a more sustainable recycling and cost-efficient manufacturing technique of polyether ketone ketone (PEKK) based thermoplastic composite materials is proposed to recover and reprocess waste and end-of-life materials in the aerospace industry. For the recycling of carbon fiber reinforced thermoplastics (CFrTP), an innovative scrapping process based on mechanical cutting was developed and the properties of the obtained scrap and the recycled panel were analyzed. Thus, a cutting tool was developed for the delamination of the input material so that long fibers can be retained in the resulting scrap. Different processing approaches of material scrapping were evaluated, aiming to obtain manageable scrap that can be subsequently used for a compression molding process. Additionally, an automatic process was evaluated to manage the scrap and perform the corresponding lay-up to manufacture high-quality thermoplastic composite products with recycled materials.